A Framework for Multi-agent System to Support Emergency Medical Services: A Review (Al-Mansour Journal, 2023)
The e-health system based on the agent system is considered one of the important and pioneering issues currently in the field of improving e-health care and the Internet of Things. Multi-agent systems have played a unique and crucial role in the interaction of mutual interdependencies, dynamic environments, uncertainty, and advanced control. There are many healthcare applications that depend on multi-agent systems. This review article presents a comprehensive review of the most current healthcare applications of multi-agent systems, by introducing multi-agent systems, their types and applications in the field of healthcare. In addition, the survey clarifies some of the literature that includes the use of smart multi-agent techniques in the field of health care and emergency cases.
Keywords: Healthcare; Multi-agent System; Emergency Medical Services